Reinterpreting Bedouin Shaabook Weaving Techniques and Materials through the Co-Creation of Omani Contemporary Jewellery - Amal Salim Khalfan Al-Ismaili (Institute of Research and Community Outreach - Petra Christian University, 2023)
The goal of this practice-based research is to create new interpretations of traditional Omani Bedouin crafts to inform the creation of contemporary jewellery. According to observations made during fieldwork with settled Bedouin craftspeople, traditional Bedouin methods for tanning leather (using plant materials such as Galqa and Qarat) and the production of leather thread for weaving are described, as is the use of weaving techniques in the production of Shaabook (headpieces), Hebla (leather belts), and traditional homemade decorative trims (Talli, Siim, and Suffah). A collaborative/co-creation workshop with a group of settled Omani Bedouin in North Eastern Oman served as the basis for this research. Participants in the workshop had a variety of traditional weaving techniques under their belts. Working in teams, the participants wove modular elements that were then combined to form a neckpiece. Using reflective analysis, the issue of hybridity is investigated in order to establish a link between the past and the present in the creation of contemporary Omani jewellery pieces.